Assessing Usability and User Experience of the KlikDokter Mobile Health Application in Indonesia - Gumelar, Agdhan Ferdian; Wulandari, Respati (Health Science UDINUS, 2025)
The use of digital technology in the health sector is becoming increasingly important, especially in improving access to medical services quickly and efficiently. One form of its implementation is online health service applications such as KlikDokter. However, high usage of the application does not guarantee that users are satisfied and that the application is easy to use. Therefore, this study was conducted to evaluate the usability and user experience of the KlikDokter application in Indonesia. This study is a descriptive quantitative study with a cross- sectional approach involving 392 respondents. The majority of respondents were aged 18–25 years (55.1%), had a bachelor’s degree as their highest educational attainment (66.6%), and were employed as private sector workers (48.7%). The usability evaluation using the System Usability Scale (SUS) method yielded an average score of 72,75, falling into the ‘Acceptable’ category with a grade of “C” and a rating of ‘Good.’ The user experience evaluation using the User Experience Questionnaire (UEQ) yielded positive scores across all dimensions, with the highest scores in Attractiveness (1.70), Efficiency (1.67), and Dependability (1.69). However, the Novelty aspect received the lowest score (0.5), indicating a lack of innovation in the application's appearance and features. These results indicate that KlikDokter demonstrates adequate usabilitty, but there is still room for improvement to provide a more engaging and innovative experience for users.